Effect of Job Description and Career Development in Improving Job Performance Employees of the Jatibaru Village Office - Indah Purnama Sari Simatupang (Junal Ilmu Manajemen, 2018)
This research was done in the Department of Rural Jatibaru which was a regional government institution. The purpose of this study was to analyze and Determine the effected given by the job description and career development toward employees performance. This type of research used associative research, the population were employees who worked in the Department of Rural Jatibaru as of March 2019 as many as 33 employees, random sampling with saturated samples so that the number of samples were 33 respondents. Research Data used primary sources of data and secondary data, the data collection techniques using library studies, questionnaires and observations. The technique of data analysis used multiple linear regression, classic assumption test and hypothesis test.Based on the results of the study indicated resources to that job descriptions and career development together have effected significant positive and toward the employee work performance. Job descriptions and career development have significantly effected partially toward employee performance. The coefficient of determination Showed that job descriptions and career development have very strong relationship to the work performance of employees in the Department of Rural Jatibaru. R square coefficient value (R2) of 0.775 Showed that employees worked performance was Able to be explained by job descriptions and career development by 77.50% and the others amount 22.5% could be explained by other variables did not Examined such as compensation, training, career planning, promotion and so on.